The meaning of evidence-based management to brazilian senior nurse leaders - Spiri, Wilza Carla [UNESP]; Macphee, Maura (Wiley, 2013)
Purpose: The study objective was to understand the meaning of evidence-based management for senior nurse leaders in accredited, public hospitals in the State of Sao Paulo, Brazil. Design and Method: A phenomenological approach was used to analyze interviews conducted with 10 senior nurse leaders between August 2011 and March 2012. The analytic method was developed by the Brazilian phenomenologist, Martins. Findings: Senior nurse leaders described how they critically appraise many sources of evidence when making managerial decisions. They emphasized the importance of working with their teams to locally adapt and evaluate best evidence associated with managerial decision making and organizational innovations. Their statements also demonstrated how they use evidence-based management to support the adoption of evidence-based practices. They did not, however, provide specific strategies for seeking out and obtaining evidence. Notable challenges were traditional cultures and rigid bureaucracies, while major facilitators included accreditation, teamwork, and shared decision making. Conclusions: Evidence-based management necessitates a continuous process of locating, implementing, and evaluating evidence. In this study leaders provided multiple, concrete examples of all these processes except seeking out and locating evidence. They also gave examples of other leadership skills associated with successful adoption of evidence-based practice and management, particularly interdisciplinary teamwork and shared decision making. Clinical Relevance: This study demonstrates senior nurse leaders' awareness and utilization of evidence-based management. The study also suggests what aspects of evidence-based management need further development, such as more active identification of potential, new organizational innovations. © 2013 Sigma Theta Tau International.
Keywords: Brazil; Evidence-based management; Innovation; Senior nurse leaders